TEKNIK PENYUSUNAN PERATURAN DESA DALAM RANGKA PENANGANAN PELANGGARAN OLEH ANAK DI DESA TENGGULI - Tamrin Tamrin; Sri Sudono Saliro; Hasiah Hasiah (Jurnal Pengabdian Kepada Masyarakat, 2022)
At this community service, communication methods (submission of the subject matter, which are one-way in nature) and interactive dialogue have been carried out, for which a draft Village Regulation (RaPerdes) has been provided for discussion or discussion of the RaPerdes. The conclusion is based on the PKM implementation on April 26, 2021, until July 15, 2021 (the date on which this report was compiled), that the PKM activities have answered the problems in the field and achieved the objectives of the PKM activities. In the context of the authority to stipulate village regulations regarding the handling of juvenile delinquency, it refers to the village government having absolute authority to stipulate Village Regulations regarding the handling of juvenile delinquency. As contained in Article 26 Paragraph (1), Article 26 Paragraph (2) letter d, letter f, letter g, and Article 26 Paragraph (4) letter k of Law No. 6 of 2014 concerning Villages, and Article 3 of Sambas Regent Regulation Number 7 2018 concerning Procedures for Drafting Village Regulations, which states that “The content of village regulations as referred to in Article 2 must be in accordance with the authority of the Village and is prohibited from conflicting with public interests, immorality, customs and/or the provisions of higher laws and regulations.